(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Studying leadership in the context of commercial organisations has proven to be a significant and challenging endeavour over the years. The purpose of this research is to investigate the factors that contribute to the achievements and failures of leaders in business settings. It has been shown that the presence of mental disorders in a leader is the primary reason for leadership failures. These disorders serve as a barrier to the leader’s ability to carry out their responsibilities as a leader to the fullest extent possible. Afflictions of the mind are a form of negativity that can have an effect, either directly or indirectly, on required functioning and frequently contribute to leadership failures. Because losing one’s ability to focus inward renders one clueless, losing one’s ability to focus on others renders one clueless, and losing one’s ability to focus outward may cause one to be blindsided, every leader needs to nurture this triad of awareness, in abundance and in the appropriate balance. The encouraging news is that virtually every type of focus may be improved upon and enhanced. This conceptual paper study on letting in different types of knowledge and losing your mind occasionally will make you a more caring and holistic leader as well as a student. And it might just help you get back in touch with your spiritual self.